2018
DOI: 10.1016/j.postharvbio.2017.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Model based leak correction of real-time RQ measurement for dynamic controlled atmosphere storage

Abstract: A method was developed to correct real-time measurements of the respiratory quotient (RQ) of pome fruit for gas leakage of a cool room. The method is based on a general leakage model that was simplified by performing sensitivity analysis of the contribution of the pressure driven and concentration driven gas transport terms. The analysis showed that pressure driven leakage was dominant over diffusive leakage. The methodology was validated successfully using an empty storage container at 0.4 kPa O2 and 1.3 kPa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Conference pears were harvested on 24 th of August 2018 and stored at −1 °C. After three weeks of storage in regular air, the pears were transferred into an air-tight polypropylene fruit storage container (≤300 L) in which the atmosphere was controlled using a DCA protocol according to [25]. Carbon dioxide concentration was maintained at 0.7 kPa while oxygen concentration was allowed to vary between 3 and 0.2 kPa, according to measured RQ values in the DCA protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Conference pears were harvested on 24 th of August 2018 and stored at −1 °C. After three weeks of storage in regular air, the pears were transferred into an air-tight polypropylene fruit storage container (≤300 L) in which the atmosphere was controlled using a DCA protocol according to [25]. Carbon dioxide concentration was maintained at 0.7 kPa while oxygen concentration was allowed to vary between 3 and 0.2 kPa, according to measured RQ values in the DCA protocol.…”
Section: Methodsmentioning
confidence: 99%
“…In RQ-DCA storage, RQ measurements were observed that deviate more from 1.0 than could biochemically explained. An explanation for observed RQ-values greater than 1.3 was found in the leak of O2 gas into the storage room during RQ-measurement (Bessemans et al, 2018). However, in RQ-DCA storage, RQ values lower than 0.7 were observed, which remain inexplicable until now.…”
Section: Introductionmentioning
confidence: 96%
“…The principle of using RQ as a biological response to detect low O2 stress has been known for many years (Wollin et al, 1985;Wolfe et al, 1993), but had not been used commercially as gas leakage of the storage environment corrupts the measurements. This problem was solved by the development of a model-based leak correction measurement, allowing real-time correction of measured RQ-values for leakage of the storage environment (Bessemans et al, 2018) and, alternatively, by the enclosure of fruit in RQ measurement chambers within or connected to the CA room (Schaefer and Bishop, 2014;Brackmann, 2015) .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, use of a dynamic, rather than a static, controlled atmosphere has gained attention. In dynamic controlled atmosphere (DCA) systems, the storage conditions are registered by monitoring the physiological response of fruits such as in a dynamic controlled atmosphere-respiratory quotient (DCA-RQ) system [ 13 , 14 , 15 , 16 , 17 ]. A limitation of a DCA-RQ system is leakage of the storage facility because a small leak from the storage room will lead to erroneous values of RQ [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…A limitation of a DCA-RQ system is leakage of the storage facility because a small leak from the storage room will lead to erroneous values of RQ [ 18 ]. Bessemans [ 13 ] introduced a new automatic DCA control system based on online real-time RQ measurements that took into account leakage in a predictive model. However, since the variability of the gas tightness of a commercial CA storage is not predictable, the mathematical model could be prone to errors.…”
Section: Introductionmentioning
confidence: 99%